Let's call the original number "x".
According to the problem, we first decrease this number by 7:
x - 7
Then, we multiply the result by 3 to get -9:
3(x - 7) = -9
We can simplify this equation by distributing the 3:
3x - 21 = -9
Now, we can add 21 to both sides of the equation to isolate the variable:
3x = 12
Finally, we divide both sides by 3 to solve for x:
x = 4
Therefore, the original number was 4.
A number is decreased by seven. Then, the new number is multiplied by 3 to get an answer of -9.
What is the original number?
1 answer